Final Report: Phase II Geothermal Exploration and Geothermal Power Plant Update for Ascension Island, South Atlantic Ocean - Nielson, D. L.; Sibbett, B. S.; Shane, M. K.; Whitbeck, J. F. (Geothermal Energy Program (U.S.), 1984)
The Phase I study of the geothermal potential of Ascension Island concluded that the possibility of a geothermal resource existing under the island was excellent. This conclusion was based on the presence of young volcanic rocks (a heat source close to the surface), an ample supply of water from the sea, and high permeability of many of the rocks which make up the island. The assumption was made that the resource would be similar to geothermal systems in the Azores or Japan, and a conceptual design of a power plant to utilize the resource was prepared upon which cost estimates and an economic analysis were subsequently performed. The results of the economic analysis were very favorable, and the Air Force decided to proceed into Phase II of the project. Under Phase II, an exploration program was designed and carried out. The purpose of the program was to ascertain whether or not a geothermal resource existed beneath Ascension island and, to the extent possible, to evaluate the quality of that resource. The exploration involved a detailed aeromagnetic survey of the island, reconnaissance and detailed electrical resistivity surveys, and drilling of holes for the measurement of temperatures. These methods have confirmed the existence of geothermal activity beneath Ascension. Measured temperature gradients and bottom hole temperatures as well as chemical geothermometers indicate temperatures sufficient for the generation of electricity within reasonable drilling depths. This report documents those conclusions and the supporting data. This report also documents the results of the power plant update with new data supplied from the Phase II exploration activities on the island. The power plant scenario has been changed to reflect the fact that the resource temperature may not be as high as that originally assumed in the Phase I study, the location of the production wells will in all likelihood be farther from the existing Air Force facilities--either north of Grazing Valley or south of Traveller's Hill--and the demand for power has increased which results in a more efficient utilization of the geothermal resource. The power plant concept chosen is similar to that used for Phase I in that small, modular, skid-mounted, factory assembled and tested, units are used to supply the power and potable water.